Assessment of effectiveness and safety of biosimilar infliximab (CT-P13) in a real-life setting for treatment of patients with active rheumatoid arthritis or ankylosing spondylitis. (3rd October 2018) - Codreanu, Cătălin; Šírová, Klára; Jarošová, Katerina; Batalov, Anastas
Abstract: Objective: To assess the effectiveness and safety of infliximab biosimilar, CT-P13, administered in a real-life setting to adult patients with active rheumatoid arthritis (RA) or ankylosing spondylitis (AS). Methods: This multi-center, non-interventional, observational study was conducted in Bulgaria, the Czech Republic, and Romania. A total of 151 patients with severe active RA ( n = 81) or AS ( n = 70) were enrolled and treated with CT-P13 for 24 weeks, according to current medical recommendations. Effectiveness was assessed using the 4-item Disease Activity Score 28 with C-reactive protein (DAS28-CRP) for RA patients, and the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) for AS patients. Safety was assessed by withdrawals and adverse events (AEs). Results: A total of 129 patients (RA: 67; AS: 62) were included in the effectiveness analysis. CT-P13 treatment significantly improved DAS28-CRP scores at 12 and 24 weeks ( p = .0001 vs baseline for both timepoints) in patients with RA and BASDAI scores at 12 and 24 weeks ( p = .0001 vs baseline for both timepoints) in patients with AS. CRP levels were significantly reduced at 12 and 24 weeks ( p = .0001 vs baseline for both timepoints). Among 713 infusions, 34 AEs were reported (4.8% of infusions), of which 11 were considered related to CT-P13 treatment. Two of seven serious AEs were considered possibly (hepatocellular injury) or definitely (dyspnoea due to allergic infusion reaction) treatment-related. Eight patients discontinued CT-P13 due to AEs and four patients were withdrawn due to therapeutic failure. Conclusions: CT-P13 was effective and safe in a real-life setting in patients with active RA or AS.